2018
DOI: 10.1080/19396368.2018.1446229
|View full text |Cite
|
Sign up to set email alerts
|

Treating donor cells with 2-PCPA corrects aberrant histone H3K4 dimethylation and improves cloned goat embryo development

Abstract: SCNT: somatic cell nuclear transfer; H3K4me2: H3K4 dimethylation; 2-PCPA: trans-2-Phenylcyclopropylamine; LSD1: lysine-specific demethylase 1; GFFs: goat fetal fibroblast cells; IVF: in vitro fertilization; iPS: induced pluripotent stem; PBS: phosphate-buffered saline; IVM: in vitro maturation; RNAPII: RNA polymerase II; HMTs: histone methyltransferase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This result also demonstrated that, unlike the process in IVF embryos, epigenetic reprogramming in somatic cells is incomplete, leading to abnormal development in SCNT embryos. The researchers attempted to implement some repair means to correct the reprogramming of somatic cells and the aberrant development of cloned embryos [ 39 , 40 ]. Previous studies have found that somatic cell reprogramming and the developmental competence of cloned embryos were improved by correcting epigenetic modifications [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result also demonstrated that, unlike the process in IVF embryos, epigenetic reprogramming in somatic cells is incomplete, leading to abnormal development in SCNT embryos. The researchers attempted to implement some repair means to correct the reprogramming of somatic cells and the aberrant development of cloned embryos [ 39 , 40 ]. Previous studies have found that somatic cell reprogramming and the developmental competence of cloned embryos were improved by correcting epigenetic modifications [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those that have been tested include cells stemming from several types of tissues collected from both caprine fetuses and adult animals of both sexes and of different ages. Among the nuclear donor cells (NDCs) used for SCNT procedures, mention should be made of: (1) in vitro cultured (transgenic or nontransgenic) fetal dermal fibroblasts [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]; (2) juvenile and adult dermal fibroblasts [ 14 , 23 , 24 , 25 , 26 ]; (3) mural granulosa cells isolated from antral ovarian follicles [ 18 , 27 ]; (4) cumulus oophorus cells [ 18 , 27 , 28 ].…”
Section: Key Issues Related To Biological Molecular and Epigenetic Determinants Affecting The Efficacy Of Somatic Cell Cloning In Goatsmentioning
confidence: 99%
“…One of the strategies to reverse advanced alterations in the pattern of epigenetic covalent modifications within somatic cell nuclei, which encompass rapid DNA methylation and a decrease in the quantitative profile of histone protein acetylation, appears to be the exposure of NDCs, SCNT-derived oocytes, and corresponding embryos to reversible agents inhibiting biocatalytic activity of DNA methyltransferases (DNMTs) and/or histone deacetylases (HDACs). The use of nonselective or selective promoters of epigenetically determined transcriptional activity of genomic DNA in both in vitro cultured NDCs and cloned embryos is supposed to be an approach that allows for proper reprogramming of somatic cell nuclei [ 7 , 12 , 14 ]. Exogenously modulating the epigenetic memory profile of genomic DNA appears to contribute to successfully reversing the “transcriptional clock” of a differentiated somatic cell nucleus to the status of a cell nucleus characteristic of a totipotent or pluripotent embryonic cell.…”
Section: Key Issues Related To Biological Molecular and Epigenetic Determinants Affecting The Efficacy Of Somatic Cell Cloning In Goatsmentioning
confidence: 99%
See 2 more Smart Citations